Discrimination between bacterial species by ratiometric analysis of their carbohydrate binding profile. Issue 2 (9th December 2015) - Otten, Lucienne; Fullam, Elizabeth; Gibson, Matthew I.
Abstract : 'Barcoding' how bacteria bind to simple sugar-surfaces using a training algorithm is used as a powerful identification tool. Abstract : Antibiotic resistance is a global health concern meaning there is an urgent need for new treatments and diagnostics. Here glycosylated surfaces are used to profile the binding patterns of a range of Gram-negative, Gram-positive and mycobacteria. This enables the creation of 'barcodes' to enable identification and discrimination between the strains, which could not be achieved by single-point glycan binding and offers a new concept in bacteria detection.